Optimization Design and Control of Six-Phase Switched Reluctance Motor with Decoupling Winding Connections - Wei Qiao; Shouyi Han; Kaikai Diao; Xiaodong Sun (Applied Sciences, 2022)
In this paper, a design optimization method is proposed to reduce the current asymmetric and consequent torque ripple for a six-phase Switched Reluctance Motor (SRM). First, the inconsistent current phenomenon of the investigated SRM is introduced, and the relationship between the magnetic distribution and the phase currents is investigated by magnetic circuit analysis. Then, for the reduction in computational cost, a surrogate model is utilized to establish the response surface model between the optimization objectives and variables. Furthermore, multiobjective optimization is performed based on structural design optimization and asymmetric control, and the best design solution is selected for the drive system. Compared with the traditional symmetric control, it can be found that the proposed asymmetric control can mitigate the inconsistent phase currents and reduce the torque ripple. Finally, a prototype motor is manufactured and tested. Both the simulation and experimental results verify the effectiveness and the reasonability of the analysis and the optimization.